The subjective assessment of work and social adjustment impairments and associated psychopathologies in Japanese adult female patients with anorexia nervosa - Naoko Iida; Junko Ono; Yuki Mizuhara; Jin Narumoto (PCN Reports, 2023)
Abstract Aim Patients with anorexia nervosa (AN) sometimes undergo a chronic course, and they hardly maintain social participation. Work and social adjustment impairments are generally significantly associated with the clinical symptoms of eating disorders. Psychopathologies associated with the subjective social difficulties of patients with AN have been unclear. This study examined the association between AN psychopathologies and work and social adjustment impairments in adult female patients with AN. Methods This study included 36 Japanese adult female patients with AN who completed the Work and Social Adjustment Scale (WSAS) and the Eating Disorder Inventory‐2 (EDI‐2). Spearman's rank correlation coefficient was used to assess correlations between WSAS and EDI‐2 or demographic variables. Results The mean age was 31.8 years, the mean current body mass index was 13.4 kg/m2, and the median illness duration was 5 years. Patients demonstrated social difficulties, especially in social leisure activities. The total WSAS scores were significantly correlated with EDI‐2 “impulse regulation” and “asceticism.” WSAS “social leisure” was significantly correlated with EDI‐2 “bulimia,” “interoceptive awareness,” “impulse regulation,” and “asceticism.” Conclusion Psychopathologies, such as impulse regulation, asceticism, and interoceptive awareness, may be related factors to social difficulties. Emotion regulation, such as impulse regulation and emotional awareness, could be an important realm of treatment not only for psychopathology but also for social functioning in patients with AN.